Comprendere e valorizzare la complessità di una storia culturale dell’educazione - Pancera, Carlo (TransCulturale, 2022)
Approaching trans-cultural issues in educational relations – re-constructed through historiography, re-imagined in current events – means first and foremost entering a very wide and dense field of complexity. Especially since it is a relatively recent field of study and research that could (and should) be approached from several perspectives (with corresponding methodologies). The fact that it reflects a new approach characterises it as a branch of our humanities disciplines that are still being shaped. Certainly, trans-culturality is an approach that by its very nature calls for a connection between inter- and trans-disciplinary views and perspectives.